Extensions of partial fuzzy metrics - Savchenko, A. (Carpathian Mathematical Publications, 2010)
It is proved that there exists a continuous extension operator for stationary partial fuzzy metrics. The main result is a counterpart of a theorem of E. Tymchatyn and M. Zarichnyi for fuzzy metrics.